FROM NORMATIVE COMMITMENT TO EFFECTIVE ACCOUNTABILITY: RECONSTRUCTING STRUCTURAL REMEDIES FOR CORPORATE CRIMINAL LIABILITY IN INDONESIA - Tumian Lian Daya Purba; Silvester Magnus Loogaman Palit; Ali Rahman; Yassine Chami (Universitas Syiah Kuala, 2026)
Indonesia’s corporate criminal liability has transitioned from fragmented sectoral laws to general codification under the New Criminal Code (Law 1/2023) and Law 1/2026. Despite this legal context, a significant legal gap remains: a persistent